Temporal imprecision and its dynamics in schizophrenia - Stephan Lechner; Ming H. Hsieh; Yi-Ting Lin; Chih-Min Liu; I-Fei Chen; Chen-Chung Liu; Yi-Ling Chien; Tzung-Jeng Hwang; Hai-Gwo Hwu; Georg Northoff (Translational Psychiatry)
Abstract Schizophrenia is a complex mental disorder whose pathophysiological mechanisms remain yet unclear. Various lines of evidence converge on a temporal disorder with temporal imprecision occurring in the millisecond range of the ongoing phase cycles. However, the intertrial phase coherence (ITPC) often used to index such temporal imprecision in EEG, is by itself not able to capture temporal irregularities in the range of around 10 milliseconds. This is due to its static calculation with the averaging over trials. To obtain a more dynamic measures in the millisecond range, we introduce 1. The precision index (PI) as temporally more precise measure, and 2. a novel more dynamic method to calculate the ITPC in temporally resolved way, i.e., dITPC. We show that schizophrenia subjects show decreased PI during deviant tones in an auditory oddball task which shows strong but not one to one correlation with the ITPC. Moreover, we demonstrate that schizophrenia subjects showed higher latencies and frequencies over the course of time in the dITPC. Finally, employing multiple regression models, we show that the latency of the dITPC, as calculated dynamically across both standard and deviant tones, predicts the PI deficits in the deviant tones. Together, our findings demonstrate temporal alterations in the phase dynamics of schizophrenia with temporal irregularities in the dynamic background predicting temporal imprecision in the lower millisecond range in the more cognitive foreground.